Gastrointestinal Effects on the Antioxidant and Immunomodulatory Properties of South African Fynbos Honey - Innocentia Botlhale Magoshi; Anwani Wendy Nekhumbe; Mohammed Auwal Ibrahim; June Cheptoo Serem; Megan Jean Bester (International Journal of Food Science)
The Fynbos biome, Western Cape Province, South Africa, produces a unique honey from Apis mellifera capensis. The bioactivity of Fynbos (FB1-FB6) honeys and Manuka, unique manuka factor 15+ (MAN UMF15+) honey subjected to simulated in vitro digestion, was compared. The effect of each phase of digestion on the antioxidant properties and nitric oxide- (NO-) associated immunomodulatory effects was determined. The total phenolic content of MAN (UMF15+) was higher than that of FB honeys, and following digestion, the percentage bioaccessibility (BA) was 68.6% and 87.1±27.0%, respectively. With the Trolox equivalent antioxidant capacity assay, the activity of FB1 and FB6 was similar to MAN (UMF15+) but reduced for FB2, FB3, FB4, and FB5 with a %BA of 77.9% for MAN (UMF15+) and 78.2±13.4% for FB. The oxygen radical absorbance capacity of MAN (UMF15+) and FB honeys was similar and unaltered with digestion. In a cellular environment, using colon adenocarcinoma (Caco-2) cells, both undigested and the gastric digested honey reduced 2,2′-azobis-(2-amidinopropane) dihydrochloride- (AAPH-) mediated peroxyl radical formation. In contrast, following gastroduodenal digestion, the formation of reactive oxygen species (ROS) was increased. In murine macrophage (RAW 264.7) cells, all honeys induced different levels of NO which was significantly increased with digestion for MAN (UMF15+) and FB1. In LPS/IFN-γ stimulated RAW 264.7 macrophages, only undigested MAN (UMF15+) effectively reduced NO levels, and with digestion, NO scavenging activity of MAN (UMF15+) was reduced but increased for FB5 and FB6. In a noncellular environment, MAN (UMF15+), FB1, FB2, and FB6 scavenged NO, and with digestion, this activity was maintained. This study has identified that undigested and gastric-digested FB honey has antioxidant properties with strong potential anticancer effects following gastroduodenal digestion, related to ROS formation. MAN (UMF15+) had anti-inflammatory effects which were lost postdigestion, and in contrast, FB5 and FB6 had anti-inflammatory effects postdigestion.